Raman scattering from InGaAs/GaAs quantum dot structures grown by atomic layer molecular beam epitaxy - Choi, WJ; Rho, H; Song, JD; Lee, JI; Cho, YH (ELSEVIER, 2005)
We report Raman scattering studies of optical phonons in InGaAs/GaAs quantum dot (QD) structures grown by atomic layer molecular beam epitaxy to explore formation of QDs and relaxation of strain. The QDs were grown by alternate supply of InAs and GaAs with deposition periods of n = 3, 5, and 7. Raman scattering reveals longitudinal optical (LO) and transverse optical phonon responses related to the sample structure. Importantly, a Raman response at similar to237cm(-1) was observed. This Raman response is attributed to the InAs-like LO phonons of InGaAs QDs, indicating clear evidence of the formation of the QDs. Moreover, both the GaAs and the GaAs-like LO phonon energies are shifted downward with increasing n from 3 to 7, suggesting that the strain relaxation occurs and the QDs grow in size. (C) 2004 Published by Elsevier B.V.
Keywords: STRAIN DISTRIBUTION; OPTICAL PHONONS; PHOTOLUMINESCENCE; RELAXATION; DEPENDENCE